1999
DOI: 10.1093/rheumatology/38.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of free and peptide-bound pyridinoline cross-links excretion in rheumatoid arthritis and osteoarthritis

Abstract: The menopause, RA and OA may have different effects on the urinary excretion of free and peptide-bound pyridinoline cross-links.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 2 publications
1
14
1
2
Order By: Relevance
“…Einerseits werden Demineralisationsprozesse der Wirbelkörper, die im Rahmen eines reduzierten Knochenstoffwechsels (? low turnover) auftreten sollen, vermutet, (26). Andererseits werden auch gesteigerte Abbauvorgänge im Sinne eines high turnover für das Entstehen der Osteoporose bei AS angeschuldigt (15,24,25,27).…”
Section: Collagen Breakdown In Ankylosing Spondylitis -Relationship Tunclassified
See 1 more Smart Citation
“…Einerseits werden Demineralisationsprozesse der Wirbelkörper, die im Rahmen eines reduzierten Knochenstoffwechsels (? low turnover) auftreten sollen, vermutet, (26). Andererseits werden auch gesteigerte Abbauvorgänge im Sinne eines high turnover für das Entstehen der Osteoporose bei AS angeschuldigt (15,24,25,27).…”
Section: Collagen Breakdown In Ankylosing Spondylitis -Relationship Tunclassified
“…unerwünschte Medikamentenwirkungen könnten zusätzlich eine entscheidende Rolle spielen (9). Eine weitere Erklärungsmöglichkeit ist eine durch abnehmende Mobilität und Schmerzen verursachte Inaktivität (26).…”
Section: Collagen Breakdown In Ankylosing Spondylitis -Relationship Tunclassified
“…Some studies have shown an increase in the markers of bone turnover, including patients with involvement at different locations such as the hip, spine, and hand. [5][6][7][8][9][10][11][12] A study by Hunter et al [17] reported that among markers of bone turnover, BALP osteocalcin, and CTx and NTx (N-and C-terminal collagen cross-links) levels were within normal limits whereas urinary deoxypyridinoline levels were increased. Another study on patients with advanced OA (28 involving the knee and 32 involving the hip joint) showed higher serum BALP and urinary deoxypyridinoline levels.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Previous studies in patients with knee, hip, spine, and hand OA revealed contradictory results for bone formation and resorption. [5][6][7][8][9][10][11][12][13] Although most of them demonstrated that biochemical markers increased in OA, [5][6][7][8][9][10][11] some reported that there was no alteration or gradual decline in bone turnover. [12,13] Osteoarthritis affects all biomechanical dynamics of the joint, resulting in functional failure.…”
mentioning
confidence: 99%
“…There have been two reports about the fractions of free and peptide-bound forms of pyridinoline crosslinks in arthritis. In a later study, when the correlations between the fractions of crosslinks and the parameters of RA disease activity were examined, the peptide-bound crosslinks correlated most with the disease activity of RA [86]. Muller et al investigated urinary fractions of free and peptide forms of collagen crosslinks in patients with rheumatoid arthritis, osteoarthrosis, psoriatic arthritis and in healthy volunteers [87] and found that collagen degradation in RA resulted primarily in peptide bound forms.…”
Section: The Fractions Of Free Form and Peptide-bound Form Of Pyridinmentioning
confidence: 99%